Leukemia mortality in children from Latin America: Trends and predictions to 2030 - J. Smith Torres‐Roman; Bryan Valcárcel; Pedro Guerra-Canchari; Camila Alves dos Santos Siqueira; Isabelle Ribeiro Barbosa; Carlo La Vecchia; Katherine A. McGlynn; Dyego Leandro Bezerra de Souza (2020)
Abstract Background Reports suggest that Latin American and Caribbean (LAC) countries have not achieved the downward mortality trends in leukemia seen in other countries. However, updated trends remain largely unknown in the region. Given that leukemia is the leading cause of cancer-related death in LAC children, we aimed to evaluate mortality trends in children (0-14y) from 15 LAC countries for the period 2000–2017 and to predict mortality until 2030. Methods We retrieved cancer mortality data through the World Health Organization Mortality Database. Age-standardized (world standard population) rates were computed for LAC countries. Joinpoint regression analysis was used to examine trends in the mortality rates of leukemia and provide an estimated annual percent change (EAPC). Nordpred was utilized for the calculation of predictions until 2030. Results Between 2013 and 2017, the highest mortality rates were reported in Venezuela, Ecuador, Nicaragua, Mexico, and Peru. Upward mortality trends were reported in Nicaragua (EAPC by 1.2% in boys, and EAPC by 2.0% in girls), Panama (EAPC by 1.8% in boys, and by 2.7% in girls), and Peru (EAPC by 1.4% in both sexes). Puerto Rico experienced large declines in mortality among both boys (APC by − 9.7%), and girls (EAPC by − 6.0%). Forecasting models predicted that leukemia mortality between 2015 and 2030, will increase in Argentina, Ecuador, Guatemala, Panama, Peru, and Uruguay. Conclusion Leukemia mortality is predicted to increase unless efforts are made to intervene. Interventions include addressing the inequities in health care diagnosing cases earlier,, avoiding treatment abandonment, and proper supportive care such as infection control programs will reduce the mortality in a great proportion.